The Complete Guide to Uninvited Advice on Raising Children - Beaven, Alice (London Hodder & Stoughton, 2005)
Cartoons from another era, advice and hilarious captions make this a must-have book for all parents who have suffered from too much unwanted advice.
Include Illustrations
Keywords: English wit and humor, Pictorial